EVALUATION OF ECONOMIC LEARNING IN THE IMPLEMENTATION OF AN INDEPENDENT CURRICULUM USING THE CIPP MODEL IN STATE HIGH SCHOOLS IN MOJOKERTO CITY - Rofiah, Siti Khusnul; Rokhmani, Lisa; Sumarsono, Hadi (Jurnal Pendidikan Ilmu Sosial, 2024)
This research aims to evaluate economic learning in the implementation of an independent curriculum using the CIPP model in public high schools throughout the city of Mojokerto. The city of Mojokerto stands out as a city with active participation in the Independent Curriculum reaching 98%. The evaluative method is used with a qualitative approach supported by quantitative data. The results of the research show that the context aspect shows variations in the selection of Independent Policy Instruments (IKM), where SMAN 1 and SMAN 3 choose independent changing IKM, while SMAN 2 adopts independent sharing IKM. The integration of articles of the 1945 Constitution into class X economics learning outcomes aims to strengthen students' understanding of the principles of the country's economy and their application in everyday life. Evaluation of the input aspect consisting of teachers, students and infrastructure shows a sufficient level of effectiveness, reaching 68.27%. Teachers use the PMM platform to optimize learning, while students' interest in economics varies and school infrastructure needs to be improved to support more effective learning. In the process aspect, SMAN 2 stands out in implementing the self-sharing model in preparing teaching tools. However, there is variation in the quality of learning between schools, with a focus on developing teacher competence and active student participation. The effectiveness of the learning process reached an average of 75.43%, this shows the need to increase more varied teaching strategies and better interaction between teachers and students. Overall product evaluation in the form of learning outcomes shows an average of 78.33%, which indicates a sufficient level of effectiveness. This research can increase student motivation, material relevance, and consistency in assessing learning outcomes, achieving more optimal results per the objectives of the Independent Curriculum.